Pengukuran Kinerja Sumber Daya Manusia menggunakan Metode Human Resources Scorecard - Ahmad Faisal Hamid; Aviasti; Dewi Shofi M (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. Human Resource Scorecard is a Human Resources performance measurement system that links people, strategy and company performance to form a competitive and superior company. There are four perspectives in measuring the Human Resource Scorecard, namely financial, customer, internal business process and learn and growth perspectives. The stages of this research are first, identifying KPIs based on the company's business strategy, second, designing an objective strategy to define the value creation process or clarity of organizational strategy, determining steps for implementing the strategy. Third, namely weighting KPIs using pairwise comparisons, the weighting stage is carried out using Expert Choice 11 software. Fourth, a scoring system is carried out using the higher is better, lower is better method. The five scoring system results obtained were categorized into Traffic Light Systems. The results of the research were 16 KPIs divided into 5 financial KPIs, 3 customer KPIs, 5 internal bussiners process KPIs, and 3 learning and growth KPIs. The results of the company's overall employee performance in calculating the weight score for each perspective are 67.86%,. The results of measuring 16 KPIs, 3 KPIs are in the red category, 6 KPIs are in the yellow category and 7 KPIs are in the green category. Factors that cause problems are decreased employee work motivation, lack of coordination between elements in the company, evaluation of employee performance. Abstrak. Human Resource Scorecard merupakan sistem pengukuran kinerja sumber daya manusia yang mengaitkan manusia, strategi dan kinerja perusahaan guna membentuk perusahaan yang berdaya saing dan unggul. Ada empat perspektif dalam pengukuran Human Resource Scorecard yaitu perspektif financial, customer, internal bussines process dan learn and growth. Tahapan penelitian ini yaitu pertama mengidentifikasi KPI berdasarkan strategis bisnis perusahaan, kedua yaitu merancang strategi objektif untuk mendefinisikan proses penciptaan nilai atau kejelasan strategi organisasi menetapkan langkah-langkah untuk pelaksanaan strategi. Ketiga, melakukan pembobotan KPI memakai perbandingan berpasangan, tahapan pembobotan memakai software Expert Choice 11. Keempat, dilakukan scoring system dengan metode higher is better, lower is better. Kelima, hasil scoring system yang diperoleh dilakukan pengategorian Traffic Light System. Hasil penelitian sebanyak 16 KPI terbagi dalam 5 KPI financial, 3 KPI customer, 5 KPI internal bussiners process, dan 3 KPI learning and growth. Hasil kinerja karyawan perusahaan secara keseluruhan pada perhitungan skor bobot pada setiap perspektif yaitu 67,86%. Hasil pengukuran 16 KPI sebanyak 3 KPI masuk ke dalam kategori warna merah, 6 KPI masuk kategori warna kuning dan 7 KPI dengan kategori warna hijau. Faktor yang menyebabkan permasalahan yaitu menurunnya motivasi kerja karyawan, kurangnya koordinasi antar elemen di perusahaan, evaluasi terhadap kinerja karyawan.